The Development of Punishment in Indonesian Criminal Law - Darmawan, Iwan; Nugraha, Roby Satya; Sihombing, Alfies L. (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2024)
With the birth of Law Number 1 of 2023 concerning the Criminal Code, it gives great hope for the development of punishment and punishment in Indonesian Criminal Law, which in turn gives hope for the fulfillment of a sense of public justice and the establishment of criminal law that guarantees legal protection from the threat of criminal offenders who can endanger the survival of the nation and state. Efforts to fundamentally reform the Indonesian criminal law have been carried out by reforming Law Number 1 of 2023 concerning the Criminal Code. The purpose of this study is to explain in detail that the development of punishment and punishment in Indonesian criminal law has undergone a fairly long development covering the Dutch colonial period, the independence period and post-independence. In the period before independence, the development of Indonesian Criminal Law was only limited to the colonial period or the Dutch colonization period. This research uses normative juridical research method. The conclusion that can be stated is that in the period before the Dutch colonization, the development of Indonesian Criminal Law was included in the scope of the Ancient Nusantara Criminal Law contained in the Ancient Nusantara Law Books originating from the period of kingdoms in the archipelago. This research finally recommends that in addition to the ancient Indonesian criminal law originating from the period of kingdoms in the archipelago, there is also customary criminal law spread throughout Indonesia.